Analysis Of Position Tracking Using Motorcycle GPS Tracking - Putra A R; Sukoco A (Bandar Lampung University (UBL), 2017)
In addition to the city, a small town such as Malang city that is dominated by the theft of motor vehicles, especially motorcycles. Based on data from Malang Police, cases in 2012 reached 1,200 and in 2013 reached 1,188 reports of disappearances recorded. Compared to other criminal cases such as forgery, fraud, embezzlement, motorcycle theft case has a high rate. While the number of two-wheeled motor vehicle theft has the percentage of 99% of the data existing cases in 2012 and 2013. (Data from Malang Police in 2013). One way that can be used to secure the vehicle from theft criminal act is to apply the Global Positioning System (GPS) on our vehicles. GPS can be described as a global satellite navigation system based on space that provides location and time that is reliable in all weather conditions at all times and anywhere on or near the earth's surface, and where the line of sight are unimpeded from four or more GPS satellites (Analysis of the Influence of Forest Environments on the Accuracy of GPS Measurements by Using Genetic Algorithms. 2010. Ordonez Galan, C., et al). If the GPS device is applied to the motor vehicle, the position data from the GPS can be delivered simultaneously. When the bike is lost due to theft or for various other reasons, the motorcycle can be easily recovered.